Secular trends of dental status in five 70-year-old cohorts between 1971 and 2001 - Fox C, Newton JT. (Blackwell Synergy, 2006)
Dental anxiety is common in children. This study sought to determine the impact of viewing positive images of dentistry prior to a dental appointment on the anticipatory dental anxiety levels of children attending for dental treatment.